2013
DOI: 10.1073/pnas.1219198110
|View full text |Cite
|
Sign up to set email alerts
|

Uranium redox transition pathways in acetate-amended sediments

Abstract: Redox transitions of uranium [from U(VI) to U(IV)] in low-temperature sediments govern the mobility of uranium in the environment and the accumulation of uranium in ore bodies, and inform our understanding of Earth's geochemical history. The molecular-scale mechanistic pathways of these transitions determine the U(IV) products formed, thus influencing uranium isotope fractionation, reoxidation, and transport in sediments. Studies that improve our understanding of these pathways have the potential to substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
236
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(263 citation statements)
references
References 72 publications
26
236
1
Order By: Relevance
“…This report suggests that microbial U reduction, i.e., the direct enzymatic pathway, played an important role in the generation of the observed U isotope fractionation in the aquifer. A more recent field-based study at the same uranium-contaminated site (35) suggested that U immobilization was due to biomass-associated mackinawite that acts as an electron source to reduce U(VI) to U(IV). However, according to the isotope signature of the process and the present findings, biogenic mackinawite could not have acted exclusively as a reducing agent in field-stimulated bioremediation.…”
Section: Discussionmentioning
confidence: 99%
“…This report suggests that microbial U reduction, i.e., the direct enzymatic pathway, played an important role in the generation of the observed U isotope fractionation in the aquifer. A more recent field-based study at the same uranium-contaminated site (35) suggested that U immobilization was due to biomass-associated mackinawite that acts as an electron source to reduce U(VI) to U(IV). However, according to the isotope signature of the process and the present findings, biogenic mackinawite could not have acted exclusively as a reducing agent in field-stimulated bioremediation.…”
Section: Discussionmentioning
confidence: 99%
“…2). [13,15] The redox conditions of the pond promote microbial reduction of uranyl to uraninite or alternately molecular U IV that is likely to settle to the bottom of the pond and not be further transported. [64][13] The chemical structure of U IV could not be confirmed by the collected XANES spectra.…”
Section: Geochemical Controls On U Transportmentioning
confidence: 99%
“…Sediment sulfur concentrations (measured by Larson et al [4] ) and sediment Fe concentrations in the pond could allow for the precipitation of amorphous FeS, following microbial reduction of sulfate and Fe III oxy(hydr)oxides, which can abiotically reduce uranyl to uraninite or non-uraninite U IV . [4,13,15,27,65] Because of the low environmental sediment U concentrations, U XANES spectra were only obtained for the top of the tailings, toe of the tailings, pond and pond outlet (Figs S7, S8, Table S2 of the Supplementary material). Of the collected spectra, the U XANES spectrum from the pond outlet was fit with the greatest percentage of U IV (45.1 %).…”
Section: Geochemical Controls On U Transportmentioning
confidence: 99%
See 2 more Smart Citations